Large Abdominal Wall Defect Reconstruction: Revoking and Modifying the Old Technique - Viswanathan, Singaravelu (Niger J Surg, 2019)
The risk factors for abdominal wall hernia after surgery are an increase in body mass index, midline incision, incisional surgical-site infection, preoperative chemotherapy, blood transfusion, increasing age, female sex, and increasing thickness of subcutaneous tissue. Reconstructing the abdominal wall defect becomes a challenge in multiple risk factor patients. Many new mesh implants have been invented, but all fail in case of infections. We modified and re-evoked an old technique of fascia lata free graft reinforced with tensor fascia lata pedicled flap.